Effect of inhaled steroids on clinical and inflammatory parameters in children with cystic fibrosis - ÇAKIR, ERKAN; UYAN, ZS; Unluguzel Ustun, Goksenin; Haklar, G; ÇAKIR, ERKAN; OKTEM, S; ERSU, R; KARADAG, B; KARAKOC, F; DAGLI, E (My University, 2017)
Background/aim: The effectiveness of inhaled corticosteroids (ICSs) in cystic fibrosis (CF) is controversial. The aim of this study was to investigate the effect of an ICS on bronchial hyperreactivity (BHR), oxidative status, and clinical and inflammatory parameters in CF patients.